2019
DOI: 10.3390/nano9020311
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic and Magnetic Properties of Multi-Atom Doped Black Phosphorene

Abstract: Recently, substitutional doping is proved to be an effective route to induce magnetism to black phosphorene for its application in spintronics. Herein, we investigate the thermodynamic stability, electronic and magnetic properties of doped black phosphorene with multi Al or Cl atoms using first-principles calculations. We find these doped phosphorenes are thermodynamically stable at 0 K and the stability first improves and then deteriorates with the number of dopant atom increasing. Corresponding to the variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Wang's group used the first‐principles calculations to investigate the electronic and magnetic properties of Al doped phosphorene with the number of dopant atoms ranging from 1 to 4. [ 40 ] The results showed that the Al doped phosphorene exhibits the best stability when the number of Al atoms is two, exceeding which the stability of phosphorene becomes to deteriorate. The electron transfer and the strength of bonds between dopant atoms and P atoms were found to depend on the electronegativity and number of heteroatoms.…”
Section: The Theoretical Calculation For Doped Bpmentioning
confidence: 99%
“…Wang's group used the first‐principles calculations to investigate the electronic and magnetic properties of Al doped phosphorene with the number of dopant atoms ranging from 1 to 4. [ 40 ] The results showed that the Al doped phosphorene exhibits the best stability when the number of Al atoms is two, exceeding which the stability of phosphorene becomes to deteriorate. The electron transfer and the strength of bonds between dopant atoms and P atoms were found to depend on the electronegativity and number of heteroatoms.…”
Section: The Theoretical Calculation For Doped Bpmentioning
confidence: 99%
“…Second, we acknowledge the presence of intrinsic defects that are inevitable during fabrication [35,36], increasing the concentration of substitutional Carbon and Oxygen impurities, displayed in the EDS spectrum in figure 1(c). Foreign atoms create shallow states in the band gap [37], thereby decreasing the band gap to a level lower than or closer to the energy of the photon [38,39]. As a result, impurities can increase the possibility of photon absorption on the materials surface.…”
Section: Photoexfoliation Of Mosmentioning
confidence: 99%
“…However, not only pure black phosphorene but also doped-phosphorene has been explored. In a recent report K Wang et al [11] found that the BS structure stability may be obtained with Al or Cl as dopants. Regarding the electronic properties, the energy gap is modi ed when the system is Al doped, it decreases with the impurity atoms contents, nevertheless it saturates to a constant value with Cl atoms.…”
Section: Introuctionmentioning
confidence: 99%